Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 2001
DOI: 10.1115/2001-gt-0148
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Characteristics of an Integrated Cooling Configuration for Ultra-High Temperature Turbine Blades: Experimental and Numerical Investigations

Abstract: This paper deals with fundamental research on heat transfer characteristics inside a cooling configuration designed for an ultra-high temperature turbine nozzle. The cooling configuration adopted in this study integrates impingement cooling and pin cooling devices into one body, aiming at the enhancement of the effective area for the impingement cooling. A large-scaled test model of this cooling system is constructed to measure its internal heat transfer distribution, where a number of pins are sandwiched betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Uniform velocity distribution ( U in ) was assumed over the inlet plane. The previous study by Funazaki et al [2] examined the validity of this assumption, reaching a conclusion that the uniform inlet velocity distribution was an acceptable assumption, at least in their test case. Inlet turbulence kinetic energy was set to be 0.01U in 2 and initial dissipation rate was k d in 2 0 05 .…”
Section: Boundary Conditions and Test Conditionsmentioning
confidence: 98%
See 3 more Smart Citations
“…Uniform velocity distribution ( U in ) was assumed over the inlet plane. The previous study by Funazaki et al [2] examined the validity of this assumption, reaching a conclusion that the uniform inlet velocity distribution was an acceptable assumption, at least in their test case. Inlet turbulence kinetic energy was set to be 0.01U in 2 and initial dissipation rate was k d in 2 0 05 .…”
Section: Boundary Conditions and Test Conditionsmentioning
confidence: 98%
“…One jobs usually converged in about 24 cpu hours. Figure 4 exhibits comparisons between the experimental heat transfer obtained for the cooling device configuration of Case 1 and H d = 1 [2][3] and its numerical counterparts calculated using the abovementioned five turbulence models. Note that uncertainty of the experimental data was estimated to be about 6% [2].…”
Section: Computational Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Quan et al [10] measured the cooling performance of an impingement system combined with pin fins by using infrared technology, and the overall cooling effectiveness was above 0.8. Funazaki et al [11,12], Son, et al [9] and Yamawaki et al [13] investigated the impingement cooling combined with circular pin fins by using transient liquid crystal technology. Their results showed that the wetted-area averaged Nusselt number of pin-fin roughened target plate was lower than flat plate; however the total heat transfer quantity of the pin-fin roughened plate increased by up to 50%, and the maximum pressure loss only increased by 10%.…”
Section: Introductionmentioning
confidence: 99%